TRANSFORMASI BUDAYA ORGANISASI UNTUK MENDORONG PROFESIONALISME DI SEKTOR INDUSTRI KREATIF - Herlina Lusiana; Ni Luh Putu Suarmi Sri Patni; Niti Lestari; Windy Permata Suyono; Iriana Bakti; Andi Zulfikar Darussalam (EDU RESEARCH, 2025)
The creative industry has dynamic characteristics that demand flexibility and constant innovation. Organizational culture transformation is a key factor in creating a work environment that is professional, collaborative, and adaptive to market changes. This research discusses how changes in values, norms, and work practices in organizations can improve professionalism in the creative industry sector. By implementing a culture that is oriented towards innovation, openness and responsibility, companies can increase productivity and competitiveness. This study also examines the challenges and strategies that can be applied in the process of transforming organizational culture to support the sustainable growth of the creative industry.